Changing hearts and minds: theorizing how, when, and under what conditions three social influence implementation strategies work - Weiner, Bryan J.; Meza, Rosemary D.; Klasnja, Predrag; Lengnick-Hall, Rebecca; Buchanan, Gretchen J.; Lyon, Aaron R.; Mettert, Kayne D.; Boynton, Marcella H.; Powell, Byron J.; Lewis, Cara C. (Frontiers in Health Services, 2024)
BackgroundOpinion leadership, educational outreach visiting, and innovation championing are commonly used strategies to address barriers to implementing innovations and evidence-based practices in healthcare settings. Despite voluminous research, ambiguities persist in how these strategies work and under what conditions they work well, work poorly, or work at all. The current paper develops middle-range theories to address this gap.MethodsConceptual articles, systematic reviews, and empirical studies informed the development of causal pathway diagrams (CPDs). CPDs are visualization tools for depicting and theorizing about the causal process through which strategies operate, including the mechanisms they activate, the barriers they address, and the proximal and distal outcomes they produce. CPDs also clarify the contextual conditions (i.e., preconditions and moderators) that influence whether, and to what extent, the strategy's causal process unfolds successfully. Expert panels of implementation scientists and health professionals rated the plausibility of these preliminary CPDs and offered comments and suggestions on them.FindingsTheoretically, opinion leadership addresses potential adopters' uncertainty about likely consequences of innovation use (determinant) by promoting positive attitude formation about the innovation (mechanism), which results in an adoption decision (proximal outcome), which leads to innovation use (intermediate outcome). As this causal process repeats, penetration, or spread of innovation use, occurs (distal outcome). Educational outreach visiting addresses knowledge barriers, attitudinal barriers, and behavioral barriers (determinants) by promoting critical thinking and reflection about evidence and practice (mechanism), which results in behavioral intention (proximal outcome), behavior change (intermediate outcome), and fidelity, or guideline adherence (distal outcome). Innovation championing addresses organizational inertia, indifference, and resistance (determinants) by promoting buy-in to the vision, fostering a positive implementation climate, and increasing collective efficacy (mechanisms), which leads to participation in implementation activities (proximal outcome), initial use of the innovation with increasing skill (intermediate outcome) and, ultimately, greater penetration and fidelity (distal outcomes). Experts found the preliminary CPDs plausible or highly plausible and suggested additional mechanisms, moderators, and preconditions, which were used to amend the initial CPD.DiscussionThe middle-range theories depicted in the CPDs furnish testable propositions for implementation research and offer guidance for selecting, designing, and evaluating these social influence implementation strategies in both research studies and practice settings.